The conversion in the René Girard’s mimetic theory - Moreno Fernández, Agustín (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
One of the specific peculiarities of René Girard’s mimetic theory is the recovery of the concept of conversion. In this article we expose, in a detailed way, the three senses of the conversion according to his thinking: novelistic, religious and epistemological. There is an interaction between the three senses and also different significations for each other.